Long Term Outcomes of Endovascular Aortic Repair in Patients With Abdominal Aortic Aneurysm and Ectatic Common Iliac Arteries. (September 2020) - Gibello, Lorenzo; Varetto, Gianfranco; Ruffino, Maria Antonella; Peretti, Tania; Frola, Edoardo; Cieri, Enrico; Parlani, Gianbattista; Ripepi, Matteo; Rispoli, Pietro; Verzini, Fabio
Abstract : Objective: The purpose of this study was to evaluate the long term results of endovascular aneurysm repair (EVAR) in patients with abdominal aortic aneurysm (AAA) and ectatic common iliac arteries (CIAs). Methods: In a retrospective analysis of a prospectively collected database in two high volume centres, patients with AAAs undergoing elective standard EVAR were divided into two groups: those with both CIA diameters <18 mm, and those with at least one ectatic iliac artery (CIA ≥ 18 mm). Patients with an intentional external iliac artery landing zone were excluded. Primary outcomes were survival and freedom from re-intervention. Secondary end points were EVAR failure and iliac related endoleak and iliac re-intervention. Results: From 2000 to 2015, 648 patients were included in the study, 277 (43%) had at least one CIA ≥ 18 mm. Pre-operative risk factors were similar between the two groups, with the exception of chronic renal insufficiency ( p = .010) and cerebrovascular events ( p = .040), which were higher in the ectatic CIA group. At 30 days from primary procedure, there was a higher rate of type Ib endoleak in patients with ectatic iliacs ( p = .020). A statistically significant increase in the incidence of late type Ib endoleak in patients with ectatic iliac arteries was confirmed at a mean follow up of 74.8 months ( p = .01). The need for iliac related re-intervention was higher in patients with CIAs ≥18 mm (odds ratio 1.94; 95% confidence interval 1.1–3.2). Conclusion: Ectatic iliac arteries are considered suitable landing zones for EVAR, although there is an increased risk of secondary interventions in time mainly due to late CIA dilation and secondary type Ib endoleak. Patients receiving EVAR with flared iliac limbs may benefit a more intensive surveillance to avoid late failures.